Bernhard Varenius: (1622 - 1650) - Schuchard, Margret (Brill's Studies in Intellectual History Ser., 2014)
This fresh portrait of Varenius presents a young German scholar, whose books on Japan (1649), the first one from a European perspective, and on General Geography (1650) were written and published in Amsterdam and led to establishing geography as a science.